On-Campus and Fully-Online University Students: Comparing Demographics, Digital Technology Use and Learning Characteristics - Johnson, Genevieve (Journal of University Teaching and Learning Practice, 2015)
First-year university students (n = 185) completed an online questionnaire that allowed comparison of those who reported studying on-campus with those who reported studying fully-online. Independent sample t-tests compared the means of students in the two study modes on demographics, frequency of use of digital technology and metacognitive learning characteristics. Compared to students who studied on-campus, students who studied fully-online were older, more likely to be native English speakers and had lower expectations of academic achievement. Compared to students who studied fully-online, students who studied on-campus were more likely to use a computer to chat or tweet, had higher levels of extrinsic achievement motivation and expressed greater need for peer and teacher support for learning. Some differences between on-campus and fully-online students appear to be eroding; other differences persist. Implications for instructional practice are presented.